2008
DOI: 10.1021/jp805560c
|View full text |Cite
|
Sign up to set email alerts
|

Thioflavin T Hydroxylation at Basic pH and Its Effect on Amyloid Fibril Detection

Abstract: The fluorescent dye thioflavin T (ThT) is commonly used for in situ amyloid fibril detection. In this work, we focused on the spectroscopic properties and chemical stability of ThT in aqueous solution as a function of pH, temperature, and dye concentration. A reversible hydroxylation process occurs in alkaline solutions, which was characterized using a combination of UV-vis absorption spectroscopy, proton NMR, and density functional theory (DFT). On the basis of these studies, we propose a chemical structure f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
100
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 54 publications
8
100
0
Order By: Relevance
“…Accordingly, it has been shown that the in vitro fibrillation of apoSOD1 displays the characteristic fingerprint of fragmentation-assisted growth (15) with a square root dependence on [D] (7), consistent with the requirement of sample agitation to expedite the reaction (1)(2)(3)(4)10). Analogous fibrillation behavior is found for β2-microglobulin (2), yeast prions Sup35 (16) and Ure2p (17), insulin (18), WW domain (19), TI 127 (20), and α-synuclein (21). The main difference between these proteins seems to be that some are intrinsically disordered and constantly aggregation-competent by lacking the ability to hide sticky sequence material by folding.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Accordingly, it has been shown that the in vitro fibrillation of apoSOD1 displays the characteristic fingerprint of fragmentation-assisted growth (15) with a square root dependence on [D] (7), consistent with the requirement of sample agitation to expedite the reaction (1)(2)(3)(4)10). Analogous fibrillation behavior is found for β2-microglobulin (2), yeast prions Sup35 (16) and Ure2p (17), insulin (18), WW domain (19), TI 127 (20), and α-synuclein (21). The main difference between these proteins seems to be that some are intrinsically disordered and constantly aggregation-competent by lacking the ability to hide sticky sequence material by folding.…”
mentioning
confidence: 63%
“…Growth seems, thus, controlled by the generic mechanical properties of the fibrils themselves rather than by their precise structural composition or environmental location. Fragmentation control is accordingly observed as a general feature on stirring, shaking, or sonication in vitro and for a variety of proteins (2,16,17,19,20) and peptides (18,21,29,30) with little or no sequence similarities. The corresponding source of mechanical stress in vivo (26) could be vascular pounding, cytoskeleton dynamics, spatial restriction of linear growth, or even chaperones in the disaggregation machinery (34).…”
Section: Discussionmentioning
confidence: 99%
“…This hydroxylation can in some cases explain the linear decrease in ThT intensity that is frequently seen after the elongation phase has ended ( Figure 5(B)). While hydroxylation is accelerated by elevated temperatures and basic conditions, it should not be discounted at neutral pH and 37 C: 15 h of incubation at 50 C reduces ThT absorbance by $25% and this is attributed to hydroxylation [95]. Alternatively, fibrillation under extreme conditions, which affect ThT emission properties can be examined using fixed time point assays, where the protein is incubated under extreme conditions and aliquots are withdrawn at fixed time points and diluted into ThTcompatible measuring conditions [96], see following section for more explanation.…”
Section: Extreme Ph Affects Thtmentioning
confidence: 99%
“…In contrast to previous studies (Foderà et al 2008), the free base amino acids l-arginine (Arg) or l-lysine (Lys) were used to raise the solution pH. In the control experiments, l-arginine hydrochloride and l-lysine hydrochloride solutions were used to exclude the direct effect of amino acids on the ThT molecule.…”
Section: Uv-vis Absorbance Of Tht In Aqueous and Buffer Solutions Witmentioning
confidence: 99%
“…For instance, in Jha et al (2014), ThT and Nile Red dyes were used to study the pH dependence of amylin fibrillation; the authors of Sabaté et al (2008) investigated the interaction of ThT with fibrils of the prion-forming domain of the fungal HET-s protein at pH 2. The effect of basic pH (made using potassium buffer solutions) on ThT fluorescence was studied in Foderà et al (2008). In that work, the authors showed that a reversible hydroxylation process occurs in alkaline solutions leading to a decrease in the ThT fluorescence signal.…”
Section: Introductionmentioning
confidence: 99%